INCREASING CAREER SELF EFFICACY THROUGH THE APPLICATION OF CLASSICAL GUIDANCE USING CINEMA THERAPY IN CLASS XI MIPA 1 SMA NEGERI 1 PURI - Edy Sucahyono (Jurnal Scientia, 2022)
Self-efficacy is a person's inner belief in his ability to organize and take actions in order to achieve the desired results. The problem of low self-efficacy in choosing a career is something serious because it is related to the future and aspirations of students. This study uses classical guidance services with the use of cinema therapy to increase low self-efficacy towards career selection in Class XI MIPA 1 students at SMA Negeri 1 Puri. The purpose of this study was to describe the low level of self-efficacy towards career selection before and after being given classical guidance with the use of cinema therapy. This research is a classroom action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The population in this study were all students of Class XI MIPA 1 at SMA Negeri 1 Puri, which consisted of 34 students. The results showed that 34 students who became the research sample had a self-efficacy level of 52.25% (low category) before receiving classical guidance services using cinema therapy. After receiving classical guidance services using cinema therapy, the average percentage of self-efficacy in choosing a career increased and entered the high category. There are differences in the level of self-efficacy towards career selection before and after the implementation of classical guidance services with the use of cinema therapy.